Human-macaque conflict and pest behaviours of longtailed macaques (Macaca Fascicularis) in Terendak Camp, Melaka, Malaysia - Kesavan Thiyagarajan (2019)
Human-macaque conflicts and the pest behaviour of long-tailed macaques (Macaca fascicularis) were studied at Terendak Camp, Melaka. The study location was focused at MRSM Terendak Camp and observation of macaque’s pest behaviours were studied from 0800 hours until 1800 hours for 5 days a week for a about 40 days from July 2018 until August 2018 inclusive by intensive direct observations using the interval scan sampling method. In addition, the survey based on questionnaire were carried about the knowledge, opinion, and attitudes towards macaques by people. The most monitored pest behavior of long-tailed macaques was breaking into residence (42.93%), followed by messing up garbage cans (17.76%), damaging property (13.72%), littering (12.74%), disturbing people (11.61%) and the lowest was stealing (1.24%). In total, 70 out of 100 (70%) questionnaires were collected. The questionnaires were dispersed randomly to MRSM students. The questionnaire survey revealed that about 98.6% of respondent claimed that they aware about the ongoing human-macaque conflict at MRSM Terendak Camp and used to their disturbance. The results shows that the pest behaviour of macaques related to foraging anthropogenic food. This study is important to understand the pest behavior of long-tailed macaques at the study area which can lead to the pest management and conservation of the species in the future. Therefore, the authorities should take some action to reduce the disturbance. In order to solve this problem local authority, school management and Wildlife Department and National Park (PERHILITAN) need to work together and come up with solution. The government and non-governments organization need to cooperate in forming a buffer zone for macaques so that can reduce the disturbance at the study area. The school management has implemented the anti-monkey bins replacing the normal garbage bins to reduce the pest behavior of macaques and replace the cascading glass windows with fully enclosed ones to prevent monkeys sneaking through the gaps.